The Results of the Clinical Nursing Guideline for Discharge Planning in Chronic Obstructive in Pulmonary Disease Patients Receiving Treatment at Kantang Hospital, Trang Province - Kan-In, Tichakorn; Songtub, Arjin (Journal of Health Science of Thailand, 2019)
This quasi experimental study was conducted to determine the results of clinical nursing guideline for discharge planning in chronic obstructive pulmonary disease patients receiving treatment at Kantang Hospital, Trang Province, measured by recurrence in 28 days of patients. The samples were chronic obstructive pulmonary disease patients recruited from 3 wards including male ward, female ward, and special ward admitted between January and September, 2016. Research instruments for data collection included general information form and treatment form which consisted of discharge planning guideline using D-METHOD criteria. Data were analyzed using frequency, percentage, Pearson Chi-Square test. The study found that 161 patients in the age range of 32-87 years were mostly patients in the age group of 41-60 years, 83.2 percent, male 85.1 percent, and 88.8 percent married. 87.0% did not work, 67.7% length of stay, less than 3 days, 64.0%. The disease duration was more than 10 years, the highest over 10 years was 50.3%. Get 27.3% of new cases of patients with chronic obstructive pulmonary disease who received discharge planning less than not get it 72.2%. The old cases patients who were received discharge planning more than not get at 54.0% and readmitted in 28 days, and news cases did not readmitted in 28 days, and found no difference in the patients who are and are not received discharge planning . It was not statistically significant at 0.05.